THE IMPORTANT ROLE OF GOVERNMENT SUPPORT ON SMALL AND MEDIUM ENTERPRISES INTERNATIONAL PERFORMANCE - M. Elfan Kaukab (Sekolah Tinggi Ilmu Ekonomi Semarang, 2022)
The contribution of Indonesian SMEs to national exports is relatively low compared to other ASEAN countries, which only around 17%. The small number of SMEs engaged in the international marketing is caused by several reasons, including the SMEs’ low entrepreneurship orientation and SMEs’ low network capability. Thus, the government’s supports in the forms of policies, incentives, and programs are expected to strengthen the SMEs’ international performance. This research aims to analyze the effect of the international entrepreneurship orientation and the SMEs’ network capability on the SMEs’ international performance. It also aims to analyze the moderation effect of the government’s supports on the causal relationship between international entrepreneurship orientation and SMEs’ network capability on SMEs’ international performance. The sample of this research is 160 SMEs producing furniture and handicrafts that have engaged in international marketing for at least 3 years. The analytical tool used in this study is moderating regression analysis using interaction method. The results show that international entrepreneurship orientation positively affects the SMEs’ international performance, network capability has a positive effect on international performance, the government’s supports strengthen the effect of international entrepreneurship orientation, and that the government’s supports weaken the effect of network capability on SMEs’ international performance.